2018
DOI: 10.14419/ijet.v7i4.34.23888
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance Mechanism, Company Size Financial Performance and Sustainability Reporting

Abstract: The importance of sustainability reporting for companies to be able to know the role of the company in disclosing social responsibility and the implementation of corporate sustainability as a manifestation of corporate governance mechanisms, company size and financial performance. This study uses a stratified random sampling method for companies that have revealed sustainability reports and those that do not disclose sustainability reports. The research method uses logistic regression, with a sample of 13 non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
1
9
1
4
Order By: Relevance
“…Pemegang saham institusional dianggap memiliki power di dalam perusahaan karena umumnya mereka memiliki saham yang besar dan pastinya juga memiliki hak suara yang besar sehingga dapat mengontrol dan mendorong manajemen untuk menginformasikan terkait lingkungan sosial lebih tinggi lagi (Masud et al, 2018). Hal tersebut didukung oleh penelitian Hardika et al (2018) dan Sellami et al (2019) yang menjabarkan bahwa terdapat pengaruh institutional ownership terhadap sustainability report. Sejalan dengan Afsari et al (2017) bahwa institutional ownership berpengaruh positif terhadap pengungkapan laporan keberlanjutan.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Pemegang saham institusional dianggap memiliki power di dalam perusahaan karena umumnya mereka memiliki saham yang besar dan pastinya juga memiliki hak suara yang besar sehingga dapat mengontrol dan mendorong manajemen untuk menginformasikan terkait lingkungan sosial lebih tinggi lagi (Masud et al, 2018). Hal tersebut didukung oleh penelitian Hardika et al (2018) dan Sellami et al (2019) yang menjabarkan bahwa terdapat pengaruh institutional ownership terhadap sustainability report. Sejalan dengan Afsari et al (2017) bahwa institutional ownership berpengaruh positif terhadap pengungkapan laporan keberlanjutan.…”
Section: Pendahuluanunclassified
“…Berdasarkan teori stakeholder adanya kepemilikan institusional ini akan mendorong pengungkapan laporan keberlanjutan yang tinggi, karena dengan adanya kepemilikan tersebut otomatis dalam hal ini dapat mendorong serta mengontrol perusahaan untuk mengungkapkan laporan keberlanjutan yang baik sebagai bentuk pertanggungjawaban kepada stakeholder sehingga dalam hal ini perusahaan akan mendapatkan legitimasi dari masyarakat. Menurut penelitian yang dilaksanakan Hardika et al (2018) ditemukan bahwa terdapat pengaruh antara institutional ownership terhadap pengungkapan sustainability report. Hal ini selaras dengan apa yang ditemukan oleh penelitian Sellami et al (2019) menyatakan bahwa pemilik saham institusional justru semakin menuntut informasi terkait sustainability dan menekan perusahaan agar perusahaan tetap membangun kredibilitas dan transparansi informasi sustainability report tersebut.…”
Section: Kepemilikan Institusional Dan Pengungkapan Sustainability Re...unclassified
“…Large companies already have a good image in the community and have gained their legitimacy so they only disclose items required in their sustainability reports. The outcome of this research is matched with Diono and Prabowo [11], Hardika et al [12] and Hidayah et al [13].…”
Section: Effect Of Company Size On the Sustainability Reportmentioning
confidence: 63%
“…Bhatia and Tuli [7], Dizar et al [8], Kilic and Kuzey [9], Lucia and Panggabean [2] and Pujiastuti [10] determined that the size of company has a positive influence on sustainability report disclosure. This is not matched with Diono and Prabowo [11], Hardika et al [12] and Hidayah et al [13] who stated that the company size harms the sustainability report disclosure. They are also in contrast to Ariyani and Hartomo [14], Maryana and Carolina [15], Masum et al [16] and Rahman [17] who explained that company size does not affect the sustainability reports disclosure.…”
Section: Introductionmentioning
confidence: 60%
“…Jermsittiparsert et al, (2019) stated that the current ratio has a significant and negative effect on stock return. Artani, (2017); Hardika et al, (2018) reported that companies with high ROE are able to maintain their growth rate without borrowing or issuing additional shares. In research conducted by Petcharabul & Romprasert (2014), stated that ROE has a significant positive relationship to stock returns.…”
Section: Return On Equity Mediates the Relationship Between Debts To Equity Ratio On Stock Returnmentioning
confidence: 99%